In-depth summary of adverse events associated with Flurbiprofen: A real-world pharmacovigilance study from 2004 to 2024 using the FAERS database - Chengkai Yang; Qian Guo; Yang Cheng; Fengjing Liu; Hui Zhang; Huaxiang Wang (PLoS ONE, 2025)
Background Flurbiprofen, as a widely used nonsteroidal anti-inflammatory drug (NSAID), is commonly employed to relieve mild to moderate pain and inflammation. Understanding its adverse reactions in real-world usage is of significant importance. Methods Reports of all adverse drug events (ADEs) related to flurbiprofen were extracted from the FAERS database, covering the period from Q1 2004 to Q3 2024. These reports were standardized and analyzed using various signal quantification techniques, including Reporting Odds Ratios (ROR), Proportional Reporting Ratios (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinkage (MGPS). Finally, the association between flurbiprofen and ADEs as well as clinical medical events was assessed. Results A total of 275 cases from the target population were identified in the FAERS database, with 788 instances of adverse events (AEs) occurring across 46 organ systems. We identified not only some common adverse reactions listed in the drug’s package insert, such as acute kidney injury, nausea and vomiting, and facial edema, but also significant signals that were not mentioned in the package insert, including Dysphonia, Drug abuse, and Pancreatitis acute. The median time to onset of flurbiprofen-related AEs was 1 day (interquartile range [IQR] 0–5 days), with most AEs occurring within the first month of flurbiprofen use. Conclusion This study confirmed some common adverse reactions listed in the flurbiprofen drug package insert and identified significant unexpected adverse reactions. These findings can assist clinicians in conducting more comprehensive clinical monitoring when using the drug, thereby ensuring patient safety during treatment.